Non-Metallic Composite Materials for Bone Surgery - Chłopek, J.; Kmita, G. (Engineering Transactions, 2003)
Possibility of using non-metallic materials in biomedical applications was considered. The attention was focused mainly on polymer materials and both the carbon-carbon and carbon-reinforced polymer composites, their mechanical and biological properties. The obtained results indicate that some of these materials can be successfully used instead of metallic implants for biomechanical functions.